The Energy Union Tour – success or failure? - Pach-Gurgul, Agnieszka (Przegląd Politologiczny, 2018)
The objective of the Energy Union is to integrate 28 national energy markets, guarantee free movement of energy through the borders of the member states, implement new technologies, increase energy efficiency and renew transmission infrastructure. This project is advocated in response to the energy crisis of 2009, between Russia and Ukraine, as a result of which the gas transit to some of the EU countries was discontinued. This project, however, does not enjoy equal interest among all EU member states. This is the outcome of the national interests of some member states, which, for many years, have had good political and economic relations with the Russian Federation, particularly in the area of energy raw materials. Therefore, Maroš Šefčovič – the European Commissioner in charge of the Energy Union, organised an Energy Union Tour, i.e. a series of meetings in all the member states, taking place at the turn of 2015–2016, the objective of which was to show what the Energy Union could offer each of them. The structure of the paper was determined by the research procedure and the response to all the research questions, comprising: introduction, reflections on the security of the energy raw material supply and the projects of Energy Union and Energy Union Tour as well as the conclusions from the research and the summary.